2022
DOI: 10.3390/vetsci9110604
|View full text |Cite
|
Sign up to set email alerts
|

Use of Transversus Abdominis Plane and Intercostal Blocks in Bitches Undergoing Laparoscopic Ovariectomy: A Randomized Controlled Trial

Abstract: In humans and dogs, loco-regional anesthesia is associated with lower peri-operative opioid consumption and less related side effects. The combination of transversus abdominis plane (TAP) and intercostal blocks can be used to desensitize the entire abdominal wall in dogs. The aim of this study was to evaluate the effectiveness of TAP and intercostal blocks in bitches undergoing laparoscopic ovariectomy. Twenty client-owned bitches were enrolled in this double-blinded randomized controlled trial. After premedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…The present study demonstrated that the combination of the TAP block with inhalational anesthesia significantly reduced the requirements of isoflurane needed to maintain the anesthetic plane suitable to perform the LapOV. This result contradicts one finding of the only study on TAP for LapOV, which did not find any difference in the median EtISO with their control group [ 19 ]. However, both studies show substantial differences in their design.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…The present study demonstrated that the combination of the TAP block with inhalational anesthesia significantly reduced the requirements of isoflurane needed to maintain the anesthetic plane suitable to perform the LapOV. This result contradicts one finding of the only study on TAP for LapOV, which did not find any difference in the median EtISO with their control group [ 19 ]. However, both studies show substantial differences in their design.…”
Section: Discussioncontrasting
confidence: 91%
“…However, both studies show substantial differences in their design. For instance, while the TAP and control groups in the present study differ only in the TAP block, the comparison group in the study of Paolini et al received a fentanyl-loading dose, followed by a constant rate infusion during the inhalation anesthesia [ 19 ]. The difference in the anesthetic protocol between the groups might have biased the results, as the authors themselves noted [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations